(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines certain aspects of the development of self-development competence in future primary school teachers, including the formation and development of its component parts. One of the key tasks in improving the effectiveness of teaching is to enhance students’ cognitive activity related to their self-development competence. In the process of forming elements of this competence, students’ learning purposes are shaped, which is a significant part of the educational process. Strengthening learning activities related to the reasons for education and maintaining them actively is one of the main methods for increasing educational effectiveness. The issue of developing mathematical abilities cannot be considered separately from self-development competence. The development of this competence serves as a foundation for the formation of creative skills. Thus, these are two sides of the process of shaping a future teacher’s talent for a specific type of activity. In the complex chain of interrelations between the psychology of abilities and the psychology of creativity, certain components clearly stand out, expressing the interconnection between a person’s abilities and other psychological aspects, such as abilities and interests, abilities and inclinations.